2005
DOI: 10.1007/s00381-004-1100-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental models of brainstem tumors: development of a neonatal rat model

Abstract: Our results demonstrate that neonatal rat models for brainstem tumors can be prepared using known injection coordinates and orthotopic cell lines. Decreasing rates of maternal removal during the course of the work suggests that the method involves a learning curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…In summary, our results, along with those from other groups, demonstrate the feasibility of using an orthotopic brainstem model for pre-clinical therapeutic testing in mice [2226]. The development of a panel of tumorigenic cell sources from DIPG patients, for use in a brainstem xenograft context, will further advance this approach for identifying effective therapeutics for treating pediatric patients afflicted with this cancer.…”
Section: Discussionsupporting
confidence: 62%
“…In summary, our results, along with those from other groups, demonstrate the feasibility of using an orthotopic brainstem model for pre-clinical therapeutic testing in mice [2226]. The development of a panel of tumorigenic cell sources from DIPG patients, for use in a brainstem xenograft context, will further advance this approach for identifying effective therapeutics for treating pediatric patients afflicted with this cancer.…”
Section: Discussionsupporting
confidence: 62%
“…Many studies indicate that the C6 glioma model best mimics the cell biological stages of early glioma progression in human. Jallo et al have recently reported an experimental brainstem tumor model in neonatal rat pups and adult rats using 9L and F98 tumor cell suspensions [24,25]. In the present study, we modified the model by changing the coordinates from 1.4 mm right and 1.0 mm anterior to lambda to 0.5 mm right and 1 mm posterior to lambda in order to ensure that the lesion would be mainly in pons.…”
Section: Discussionmentioning
confidence: 99%
“…4). 56,57,65,123 Wu et al 122 demonstrated that carboplatin could be locally delivered to neoplastic cells in a rat brainstem tumor model with mini-osmotic pumps, which resulted in a prolongation of survival. Moreover, Lonser et al 71 documented the safety of locally infused Gd-bound albumin via stereotactically implanted cannulas into large areas of the primate midbrain and pons, followed by other reports showing the safety of CED of chemotherapeutic agents, such as gemcitabine and carboplatin, infused into the primate brainstem, although dose-dependent toxicity has been found with carboplatin.…”
Section: New Therapeutic Perspective Strategiesmentioning
confidence: 99%